Modeling transient particle transport in transient indoor airflow by fast fluid dynamics with the Markov chain method. (December 2020) - Liu, Wei; van Hooff, Twan; An, Yuting; Hu, Simon; Chen, Chun
Abstract: It is crucial to accurately and efficiently predict transient particle transport in indoor environments to improve air distribution design and reduce health risks. For steady-state indoor airflow, fast fluid dynamics (FFD) + Markov chain model increased the calculation speed by around seven times compared to computational fluid dynamics (CFD) + Eulerian model and CFD + Lagrangian model, while achieving the same level of accuracy. However, the indoor airflow could be transient, if there were human behaviors involved like coughing or sneezing and air was supplied periodically. Therefore, this study developed an FFD + Markov chain model solver for predicting transient particle transport in transient indoor airflow. This investigation used two cases, transient particle transport in a ventilated two-zone chamber and a chamber with periodic air supplies, for validation. Case 1 had experimental data for validation and the results showed that the predicted particle concentration by FFD + Markov chain model matched well with the experimental data. Besides, it had similar accuracy as the CFD + Eulerian model. In the second case, the prediction by large eddy simulation (LES) was used for validating the FFD. The simulated particle concentrations by the Markov chain model and the Eulerian model were similar. The simulated particle concentrations by the Markov chain model and the Eulerian model were similar. The computational time of the FFD + Markov chain model was 7.8 times less than that of the CFD + Eulerian model. Highlights: A fast fluid dynamics (FFD) ＋ Markov chain model solver developed in OpenFOAM. The solver is for predicting transient particle transport in transient indoor airflow. The developed method had a similar accuracy to the CFD ＋ Eulerian model. 7.8 times less computing time than CFD ＋ Eulerian model.